Quality‐of‐life outcomes following pelvic exenteration for primary rectal cancer. Issue 12 (16th September 2015) - Radwan, R. W.; Codd, R. J.; Wright, M.; Fitzsimmons, D.; Evans, M. D.; Davies, M.; Harris, D. A.; Beynon, J.
<x xml:space="preserve">Abstract</x> Background For patients with locally advanced tumours and contiguous organ involvement, pelvic exenteration (PE) can offer cure with relatively low mortality. The literature surrounding quality of life (QoL) in patients undergoing PE is limited. Furthermore, there are no matched comparisons of QoL between abdominoperineal resection (APR) and PE. The aim of this study was to compare differences in long‐term QoL for patients with primary rectal cancer undergoing APR versus PE. Methods All patients who underwent either APR or PE between January 2011 and December 2012 were identified. Patients were asked to complete the European Organization for Research and Treatment of Cancer QLQ‐C30 questionnaire before surgery and 2 weeks afterwards. Subsequent questionnaires were requested at 3, 6, 12 and 24 months after operation. Results A total of 110 patients were included in the study (54 APR, 56 PE). Median length of stay following operation was 11 (range 3–70) days for APR and 15 (7–84) days for PE. Patients undergoing PE experienced lower physical (mean score 42 versus 56; P = 0·010), role (20 versus 33; P = 0·047), emotional (57 versus 73; P = 0·010) and social (34 versus 52; P = 0·005) functional levels 2 weeks after surgery. Long‐term dyspnoea and financial worries were experienced only after PE. Patients undergoing PE had a lower overall global health status at 2 weeks after operation (40 versus 53; P = 0·012). Levels were comparable between groups from 3 months after surgery. Conclusion QoL recovery following PE was equivalent to that after APR alone. Patients should not be denied exenterative surgery based on perceived poor QoL.